(untitled) (Medico Legal Update, 2020)
Background: Burn Injuries constituted an important high priority health problem especially in little and medium salary republics including Iraq. Objective: Identify the characteristics of burn injuries and its outcomes among patients admitted to Al-Hilla Teaching Hospital burn unit–Babylon Province Iraq. Method: This was observational cross sectional hospital based study, burn injury data were collected from the interview of burn patients admitted to burn unit of Al Hilla Teaching Hospital,Babylon Province, Iraq during the last four months during the year 2019, using special data collection questionnaire included; burn patients demographic characteristics, period of hospital stay (days), size of total body surface areas, degrees of burn injuries, types of treatment and the outcomes. Results: The highest proportion of cases were males, the majority of patients were young adults and children, about four fifth of cases were rural dwellers (78%). The means and standard deviations of duration of hospitalization and total surface areas were 5.72+53 days and 21,9+21.1 respectively, about two thirds of the study group were second and or third degrees burn, only 12% of patients were treated surgically by wound excision and skin graft, 67% of patients were cured while the case fatality rate was 9%. Conclusion: Children, males and poorly educated patients were the majority of cases, about nine in tenth were treated conservatively and about two thirds of cases were cured.